PENGEMBANGAN VITUR SEBAGAI MEDIA PEMBELAJARAN FISIKA UNTUK MENINGKATKAN KEMAMPUAN BERFIKIR KREATIF SISWA - Irwandi Irwandi; Sukainil Ahzan; Samsun Hidayat (Lensa: Jurnal Kependidikan Fisika, 2015)
This research is purposed to develop caricatur based video as a teching media for physics subjeck to enrich student’ creative thiking ability.  The research was developed by using 4 D design which is well know as define, design, develop and disseminate. Collecting data is research. The researcher uses validity of  learning intruction test, quistionaire for students, and creative thiking ability test.  The research subject of this research is the VIII  grade students is the SMPN 5 plampang. The data analysis used in this study is descriptive qualititative approach. The result of vitur validation test shows that using  vitur as the physic teaching media to enrich students creative thiking ability can be categorized into  “valid” category in which the average score gained by the research subjects is 3,75 and the studen’ responses show the result in average 3,20. This result can be categorized  into high  category in using vitur as the physic teahing media to enrich  student’  creative thiking ability. The creative thiking ability test the was the distributed by  researcher to the reseach subjects show the result 67,25%. Ultimately, it can be inffered that vitur as the physics the teaching media is valid and properly used to enrich students’ creative thinking ability.